2020
DOI: 10.3390/ijerph17165816
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Media on Parents’ Attitudes toward Vaccination of Children—Social Marketing and Public Health

Abstract: The aim of this paper was to investigate the level of influence of online media on the parents’ attitudes toward vaccination of children in three countries of the Western Balkans—Montenegro, Serbia, and Bosnia and Herzegovina, in order to use the potentials of this form of communication effectively and efficiently. Online media are a critical factor of influence on the formation of attitudes in many areas of modern society, which is why their proper use plays an important role in strengthening vaccine confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
(89 reference statements)
1
11
0
1
Order By: Relevance
“…However, this is worrying since there is a large amount of unreliable, unverified, and contradicting information that is not peer reviewed on Internet websites about vaccination and, therefore, such information should be managed with caution [26,27]. Moreover, an evolving body of literature showed that the use of the Internet has been consistently associated with a lower level of knowledge [28][29][30], less positive attitudes, and decreased use of preventive services with, for example, lower uptake and willingness to have the vaccination [31][32][33]. Therefore, it is an important priority to ensure information and communication strategies to improve the level of knowledge and the adoption of appropriate preventive behaviors towards COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is worrying since there is a large amount of unreliable, unverified, and contradicting information that is not peer reviewed on Internet websites about vaccination and, therefore, such information should be managed with caution [26,27]. Moreover, an evolving body of literature showed that the use of the Internet has been consistently associated with a lower level of knowledge [28][29][30], less positive attitudes, and decreased use of preventive services with, for example, lower uptake and willingness to have the vaccination [31][32][33]. Therefore, it is an important priority to ensure information and communication strategies to improve the level of knowledge and the adoption of appropriate preventive behaviors towards COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the speed at which events are developing and changing during a pandemic, websites are a main medium of communication. Similarly, public health concerns regarding issues such as vaccination (Kunze et al, 2019 ; Melovic et al, 2020 ), alcohol consumption (Sahadev et al, 2020 ), nutrition (Abdi et al, 2020 ; Vaughn et al, 2019 ), disease and infection control (Bauld, 2018 ; Gallivan et al, 2007 ; Mah et al, 2006 ; Pastrana et al, 2020 ) , hand hygiene (Gould et al, 2010 ; Mah et al, 2006 , 2008 ; Wilson et al, 2011 ) , mask wearing, case contact tracing, social distancing and testing (Means et al, 2020 ), and public mental health concerns (Luck et al, 2009 ) , all of which are highly relevant during the COVID-19 pandemic, often use SM techniques to promote behavior change.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The total count scored between 0 and 8, where the higher score referred to more demand of COVID-19 vaccine. Previous studies also used some contents of these items [23,24].…”
Section: Measures and Rating Instrumentsmentioning
confidence: 99%